PRESIDEN JOKO WIDODO DALAM BINGKAI MEDIA MASSA - Suharyo, Suharyo; Surono, Surono; A, M. Farikhul (LITERA, 2017)
Abstract This study aimed to describe the ideology of: (a) journalists, (b) politicians, and (c) observers/community in framing President Joko Widodo in Suara Merdeka, Kompas, and Republika daily newspapers. The data sources were the three newspapers published in 2016. The data were collected through: (a) literature study, (b) discourse analysis, and (c) in-depth interviews with linguists and mass media experts. The data analysis was carried out using Pan and Kosicki’s framing analysis model. The results show that there are ideological differences among the three media in framing President Joko Widodo. The differences are manifested in the aspects of: (a) syntax, (b) script, (c) theme, and (d) rhetoric. The three media also differ in presenting: (a) news schemes, (b) news completeness, (c) details, (d) lexicon, and (e) completeness of 5W + 1H elements in reporting President Joko Widodo. Keywords: frame, ideology, media, framing analysis